Evaluation of posttransplant methotrexate to facilitate engraftment in the canine MHC-haploidentical nonmyeloablative transplant model - Thakar, Monica S (2010)
BACKGROUND: Posttransplant cyclophosphamide (CY) has been shown to control graft-versus-host disease (GVHD) and facilitate engraftment in the major histocompatibility complex (MHC)-haploidentical transplant setting. Here we hypothesized that methotrexate (MTX) could be used in a similar fashion. In patients with genetic diseases, the use of MTX rather than an alkylating agent such as CY would be preferable due to its reduced risk of promoting secondary malignancies. METHOD: Using our standard conditioning regimen consisting of a specific anti-CD44 MAb (S5) and 200 cGy total body irradiation (TBI) followed by postgrafting immunosuppression with cyclosporine (CSP) and mycophenolate mofetil (MMF) as a control group, we compared outcomes to experimental animals receiving the same regimen with the addition of a single, large dose of posttransplant MTX on day +3 (50–400 mg/m(2)). RESULTS: Adding MTX at all dose levels did not abrogate initial engraftment and controlled GVHD in most cases. Dogs receiving MTX at the first dose level (50 mg/m(2)) improved time to rejection compared to controls (p=0.03) but did not decrease overall rates of rejection (p=0.56). However, increasing the dose of MTX beyond 50 mg/m(2) appeared to have detrimental effects in both average (p=0.04) and peak (p=0.002) donor chimerism. Increasing the dose of MTX also promoted more profound lymphopenia. Finally, delaying CSP and MMF until after MTX administration did not appear to significantly improve engraftment kinetics. CONCLUSION: Adding high-dose MTX appeared to benefit the duration of donor chimerism at the lowest dose studied, but there was no benefit when escalating MTX doses to toxicity.